2014
DOI: 10.1089/ten.tea.2013.0495
|View full text |Cite|
|
Sign up to set email alerts
|

Combined Effects of Brain-Derived Neurotrophic Factor Immobilized Poly-Lactic-Co-Glycolic Acid Membrane with Human Adipose-Derived Stem Cells and Basic Fibroblast Growth Factor Hydrogel on Recovery of Erectile Dysfunction

Abstract: Erectile dysfunction (ED) is the most frequent long-term problem after radical prostatectomy. We aimed to evaluate whether the use of combination therapy with basic fibroblast growth factor (bFGF)-hydrogel on corpus cavernosum and with adipose-derived stem cells (ADSCs) and brain-derived neurotrophic factor (BDNF)-immobilized poly-lactic-co-glycolic acid (PLGA) membrane on the cavernous nerve (CN) could improve erectile function in a rat model of bilateral cavernous nerve crush injury (BCNI). Rats were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…bFGF is a member of the fibroblast growth factor family, which plays a significant role in the pathogenesis of several diseases including osteogenesis, adipogenesis, and normal wound healing, by inducing angiogenesis (Tabata, ). It was reported that bFGF treatment ameliorated erectile function in animal models (Suetomi et al ., ; Bae et al ., ; Lee et al ., ). Takahiro et al .…”
Section: Discussionmentioning
confidence: 97%
“…bFGF is a member of the fibroblast growth factor family, which plays a significant role in the pathogenesis of several diseases including osteogenesis, adipogenesis, and normal wound healing, by inducing angiogenesis (Tabata, ). It was reported that bFGF treatment ameliorated erectile function in animal models (Suetomi et al ., ; Bae et al ., ; Lee et al ., ). Takahiro et al .…”
Section: Discussionmentioning
confidence: 97%
“…The cavernosal nerve is distributed in the cavernous body of the urethra, corpus cavernosum and erectile tissue and is formed by the sympathetic nerve, which is the main nerve that regulates penile erection. It has been confirmed that neuropathy plays a major role in the pathophysiology of diabetic ED (Hecht, Neundorfer, Kiesewetter, & Hilz, ; Lee et al., ).…”
Section: Diabetic Neuropathy In Diabetic Erectile Dysfunctionmentioning
confidence: 89%
“…The inherent deficiency of SOD2, a potent component of the SOD family, in testicular tissues also contributes to the vulnerability of this tissue to D‐gal—induced oxidative stress. The antioxidant effects of ADSCs have been described previously (Lee et al, ). In our study, treatment with ADSCs alleviated the D‐gal—induced alteration in testicular oxidant balance.…”
Section: Discussionmentioning
confidence: 99%